2005
DOI: 10.1183/09031936.05.00142104
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake of flavonoids and asthma in adults

Abstract: Epidemiological studies have suggested that a high consumption of apples may protect against asthma and chronic obstructive pulmonary disease. This effect has been attributed to their high flavonoid content, but few studies have investigated the relationship between flavonoid intake and obstructive lung disease directly.In a population-based, case-control study of 1,471 adults aged 16-50 yrs in London (UK), the present study examined whether dietary intake of catechins, flavonols and flavones was negatively as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 27 publications
1
45
0
Order By: Relevance
“…31) Naturally occurring flavonoids with safety have attracted considerable attention as anti-allergic agents 5) suppressing Th2 cytokine production in T cells 32) as well as basophils, 33) and intake of flavonoids has been known to reduce the incidence and severity of allergies in humans. 5,6) In this study we showed that 25 mM of T-412 almost completely inhibited IL-4 production in activated T cells without affecting cell viability. T-412 suppressed the IL-4 expression at the transcriptional level, and we found that T-412 could control the selective transcription factors including NF-AT/AP-1 and c-Maf but not NF-kB.…”
Section: Discussionmentioning
confidence: 79%
“…31) Naturally occurring flavonoids with safety have attracted considerable attention as anti-allergic agents 5) suppressing Th2 cytokine production in T cells 32) as well as basophils, 33) and intake of flavonoids has been known to reduce the incidence and severity of allergies in humans. 5,6) In this study we showed that 25 mM of T-412 almost completely inhibited IL-4 production in activated T cells without affecting cell viability. T-412 suppressed the IL-4 expression at the transcriptional level, and we found that T-412 could control the selective transcription factors including NF-AT/AP-1 and c-Maf but not NF-kB.…”
Section: Discussionmentioning
confidence: 79%
“…Kotani et al [2000] reported that oral administration of flavonoids such as astragalin and kaemperol suppresses the onset of allergic disease in the atopic dermatitis of NC/Nga mice, and that the intake of flavonoids in asthmatic models leads to a significant suppression of symptoms including bronchial hyperactivity and bronchoconstriction. Intake of human traditional vegetarian diet containing flavonoids has been reported to reduce symptoms of atopic dermatitis [Knekt et al, 2002;Garcia et al, 2005]. Although fisetin has suppressive effects on Th2 cytokines in human basophils [Higa et al, 2003], its molecular mechanisms for the suppression of Th2 cytokine production in basophils and mast cells has been incompletely elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…In studies using Western diets (9,11,(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48), mean intakes from the various classes of flavonoids were about 10 mg/day for anthocyanins, 84 mg/day for flavan-3-ols, 33 mg/d for flavanones, 0.5 mg/d for flavones, 17 mg/day for flavonols, 6 mg/day for isoflavones, and 170 mg/day for total flavonoids. The women in the WINS population tended to have higher mean intakes compared to these other populations of flavan-3-ols, flavones, flavonols and lower for flavanones, perhaps because we used more complete data than were available to these earlier investigators or because we included flavonoid-containing supplements.…”
Section: Flavonoid Intakesmentioning
confidence: 98%